The PROFILE Feasibility Study: Targeted Screening of Men With a Family History of Prostate Cancer. (5th May 2016) - Castro, Elena; Mikropoulos, Christos; Bancroft, Elizabeth K.; Dadaev, Tokhir; Goh, Chee; Taylor, Natalie; Saunders, Edward; Borley, Nigel; Keating, Diana; Page, Elizabeth C.; Saya, Sibel; Hazell, Stephen; et al.
Abstract : Background: A better assessment of individualized prostate cancer (PrCa) risk is needed to improve screening. The use of the prostate‐specific antigen (PSA) level for screening in the general population has limitations and is not currently advocated. Approximately 100 common single nucleotide polymorphisms (SNPs) have been identified that are associated with the risk of developing PrCa. The PROFILE pilot study explored the feasibility of using SNP profiling in men with a family history (FH) of PrCa to investigate the probability of detecting PrCa at prostate biopsy (PB). The primary aim of this pilot study was to determine the safety and feasibility of PrCa screening using transrectal ultrasound‐guided PB with or without diffusion‐weighted magnetic resonance imaging (DW‐MRI) in men with a FH. A secondary aim was to evaluate the potential use of SNP profiling as a screening tool in this population. Patients and Methods: A total of 100 men aged 40–69 years with a FH of PrCa underwent PB, regardless of their baseline PSA level. Polygenic risk scores (PRSs) were calculated for each participant using 71 common PrCa susceptibility alleles. We treated the disease outcome at PB as the outcome variable and evaluated its associations with the PRS, PSA level, and DW‐MRI findings using univariate logistic regression. Results: Of the 100 men, 25 were diagnosed with PrCa, of whom 12 (48%) had clinically significant disease. Four adverse events occurred and no deaths. The PSA level and age at study entry were associated with PrCa at PB ( p = .00037 and p = .00004, respectively). Conclusion: The results of the present pilot study have demonstrated that PB is a feasible and safe method of PrCa screening in men with a FH, with a high proportion of PrCa identified requiring radical treatment. It is feasible to collect data on PrCa‐risk SNPs to evaluate their combined effect as a potential screening tool. A larger prospective study powered to detect statistical associations is in progress. Implications for Practice: Prostate biopsy is a feasible and safe approach to prostate cancer screening in men with a family history and detects a high proportion of prostate cancer that needs radical treatment. Calculating a polygenic risk score using prostate cancer risk single nucleotide polymorphisms could be a potential future screening tool for prostate cancer. Abstract : A better assessment of prostate cancer (PrCa) risk is needed to improve screening. The PROFILE pilot study explored the feasibility of single nucleotide polymorphism profiling in men with a family history (FH) of PrCa to investigate the probability of detecting PrCa at prostate biopsy (PB). The results of the present pilot study have demonstrated that PB is a feasible and safe method of PrCa screening in men with a FH.